PENGENALAN ANGKA ANAK MELALUI MEDIA BALOK WARNA DI RA NURUL UMMAH - Roudlotun Ni’mah; Siti Muntamah (Nahdlatul Ulama University Sunan Giri Bojonegoro, Indonesia, 2021)
This study aims to determine the implementation of the introduction of children's numbers through beam media at RA Nurul Ummah Kenep Balen, Bojonegoro Regency. This study uses a qualitative approach. Data was collected by using interview, observation, and documentation techniques. Data analysis techniques include the method of induction and descriptive/interpretive analysis, data presentation, and conclusion drawing, checking the validity of the research by extending the participation of researchers, triangulation techniques. The results showed that the introduction of children's numbers through the media of color blocks can increase the knowledge of numbers for children, and for teachers it is easier for students to understand numbers. The supporting factors are the existence of a program that has become a mandatory activity set by the school as one of the subjects, the support from the school to provide educational learning facilities in the form of color blocks, the ability of active and creative teachers to use media facilities, while the inhibiting factors are students who still cannot distinguish the color of the blocks, students are late when entering. Efforts to recognize numbers that need to be done are careful preparation for teachers before doing learning, both learning administration, teaching preparation, and learning media, especially in counting using color block media, and the presence of complementary media from color block media.